Estimations of benchmark dose for urinary metabolites of coke oven emissions among workers. (15th March 2021) - Zou, Kaili; Wang, Sihua; Wang, Pengpeng; Duan, Xiaoran; Yang, Yongli; Yazdi, Mahdieh Danesh; Stowell, Jennifer; Wang, Yanbin; Yao, Wu; Wang, Wei
Abstract: Coke oven emissions (COEs), usually composed of polycyclic aromatic hydrocarbons (PAHs) and so on, may alter the relative telomere length of exposed workers and have been linked with adverse health events. However, the relevant biological exposure limits of COEs exposure has not been evaluated from telomere damage. The purpose of this study is to estimate benchmark dose (BMD) of urinary PAHs metabolites from COEs exposure based on telomere damage with RTL as a biomarker. A total of 544 exposed workers and 238 controls were recruited for participation. High-performance liquid chromatography and qPCR were used to detect concentrations of urinary mono-hydroxylated PAHs and relative telomere length in peripheral blood leukocytes for all subjects. The benchmark dose approach was used to estimate benchmark dose (BMD) and its lower 95% confidence limit (BMDL) of urinary OH-PAHs of COEs exposure based on telomere damage. Our results showed that telomere length in the exposure group (0.75 (0.51, 1.08)) was shorter than that in the control group (1.05 (0.76, 1.44))( P  < 0.05), and a dose-response relationship was shown between telomere damage and both 1-hydroxypyrene and 3-hydroxyphenanthrene in urine. The BMDL of urinary 1-hydroxypyrene from the optimal model for telomere damage was 1.96, 0.40, and 1.01 (μmol/mol creatinine) for the total, males, and females group, respectively. For 3-hydroxyphenanthrene, the BMDL was 0.94, 0.33, and 0.49 (μmol/mol creatinine) for the total, males, and females. These results contribute to our understanding of telomere damage induced by COEs exposure and provide a reference for setting potential biological exposure limits. Graphical abstract: Image 1 Highlights: An association was shown between 1-OHP increasing and telomere length shortening. An association was shown between 3-OHPhe increasing and telomere length shortening. The biological exposure limit of 1-OHP was suggested at 0.40 μmol/mol creatinine. The biological exposure limit of 3-OHPhe was suggested at 0.33 μmol/mol creatinine.